"Maybe a little bit of guilt isn't so bad for the overall health of an individual": a mixed-methods exploration of young adults' experiences with calorie labelling - Amanda Raffoul; Brooke Gibbons; Karla Boluk; Elena Neiterman; David Hammond; Sharon I. Kirkpatrick (BMC, 2022)
Abstract Background Menu labelling, and more specifically calorie labelling, has been posited as an intervention to improve nutrition literacy and the healthfulness of consumers' food purchases. However, there is some concern calorie labelling may unintentionally trigger or exacerbate disordered eating among vulnerable persons. The purpose of this research was to explore young adults' experiences with labelling, with a focus on its implications for their relationships with food. Methods Individual semi-structured interviews were conducted with participants from a campus-based menu labelling study. Interview data were inductively coded using thematic analysis and supported by survey data assessing disordered eating, body esteem, and related constructs. Results The sample consisted of 13 participants (10 women, 3 men), most of whom perceived themselves as "about the right weight" (62%). Four key themes included: (1) participants' support of and skepticism about labelling interventions, (2) the identification of knowledge and autonomy as mechanisms of labelling interventions, (3) the role of the individual's and others' relationships with food in experiences with labelling, and (4) disordered eating and dieting as lenses that shape experiences with interventions. Participants' perceptions of and experiences with calorie labels were shaped by gender, body esteem, and disordered eating risk. Conclusions The results provide insight into the complexity of young adults' interactions with labelling interventions and context for future research exploring the unintended consequences of public health nutrition interventions.